The Heidelberg appendicitis score predicts perforated appendicitis in children - Boettcher, Michael; Günther, Patrick; Breil, Thomas (Clinical pediatrics, 2017)
Background. In the future, surgical management of pediatric appendicitis might become limited to nonperforating appendicitis. Thus, it becomes increasingly important to differentiate advanced from simple appendicitis and to predict perforated appendicitis among a group of children with right-sided abdominal pain, which was the aim of this study. Methods. An institutionally approved, single-center retrospective analysis of all patients with appendectomy from January 2009 to December 2010 was conducted. All diagnostic aspects were evaluated to identify predictors and differentiators of perforated appendicitis. Results. In 2 years, 157 children suffered from appendicitis. Perforation occurred in 47 (29.9%) of the patients. C-reactive protein (CRP) levels higher than 20 mg/dL (P = .037) and free abdominal fluid on ultrasonography (P = .031) are the most important features to differentiate perforated from simple appendicitis. Moreover, all children with perforation had a positive Heidelberg Appendicitis Score (HAS). A negative HAS excludes perforation in all cases (negative predictive value = 100%). Discussion. Perforated appendicitis can be ruled out by the HAS. In a cohort with right-sided abdominal pain, perforation should be considered in children with high CRP levels and free fluids or abscess formation on ultrasound.